2004
DOI: 10.1023/b:jade.0000035626.90331.47
|View full text |Cite
|
Sign up to set email alerts
|

Division of Labor Among Lesbian and Heterosexual Parenting Couples: Correlates of Specialized Versus Shared Patterns

Abstract: One of the central tasks that couples face in coparenting is the division of labor. In this study, we explored division of family labor among lesbian and heterosexual couples who were parenting 4 to 6 year-old children. Sixty-six families, half headed by lesbian couples and half headed by heterosexual couples, participated in the study. Measures of parental attitudes, resources, demographics, and division of labor were collected. As expected, lesbian couples were more likely to divide paid and unpaid labor eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(196 citation statements)
references
References 27 publications
13
176
2
5
Order By: Relevance
“…Sweden is often described as more gender equal than other Western societies (Ahrne, Roman & Franzén, 2003;Magnusson, 2008;Ryan-Flood, 2009), with dual earners being the most common family form, and extensive access to parental leave offered to both mothers and fathers (Sverige Statistiska Centralbyrån, 2012;Swedish Social Insurance Agency, 2012). Lesbians are typically described as forming more equal relationships than different-sex couples (Bos & van Balen, 2010;Chan et al, 1998;Ciano-Boyce & Shelley-Sireci, 2002;Goldberg et al, 2012a;Patterson, Sutfin, & Fulcher, 2004;Perlesz et al, 2010;Tasker & Golombok, 1998), thus Swedish lesbians could be expected to put great emphasis on equality. The present study shows that most participants depict equality as an ideal, where some claim that their equality was spontaneously achieved.…”
Section: Chapter VI Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweden is often described as more gender equal than other Western societies (Ahrne, Roman & Franzén, 2003;Magnusson, 2008;Ryan-Flood, 2009), with dual earners being the most common family form, and extensive access to parental leave offered to both mothers and fathers (Sverige Statistiska Centralbyrån, 2012;Swedish Social Insurance Agency, 2012). Lesbians are typically described as forming more equal relationships than different-sex couples (Bos & van Balen, 2010;Chan et al, 1998;Ciano-Boyce & Shelley-Sireci, 2002;Goldberg et al, 2012a;Patterson, Sutfin, & Fulcher, 2004;Perlesz et al, 2010;Tasker & Golombok, 1998), thus Swedish lesbians could be expected to put great emphasis on equality. The present study shows that most participants depict equality as an ideal, where some claim that their equality was spontaneously achieved.…”
Section: Chapter VI Discussionmentioning
confidence: 99%
“…This concerns questions of how household and parenting tasks are negotiated and divided among lesbian parents. Results have generally shown that lesbians are more egalitarian than different-sex couples (Bos & van Balen, 2010;Bos, van Balen & van den Boom, 2007;Chan et al, 1998;Ciano-Boyce & Shelley-Sireci, 2002;Goldberg, Smith & Perry-Jenkins, 2012a;Patterson, Sutfin & Fulcher, 2004;Perlesz et al, 2010;Tasker & Golombok, 1998). Still, some studies point out that the positions as birth mother and non-birth mother, respectively, tend to form divided parental roles, with the birth mother being the main caregiver and the non-birth mother the main breadwinner Ciano-Boyce & Shelley-Sireci, 2002;Downing & Goldberg, 2011;Goldberg & Perry-Jenkins, 2007;Patterson, 1995).…”
Section: Studies On Lesbian Family Life and Practicesmentioning
confidence: 99%
“…It involves far more than just the carrying out of childcare responsibilities (McHale, 1995;McHale & Fivaz-Depeursinge, 1999;McHale, Khazan, et al, 2002;McHale, Lauretti, Talbot, & Pouquette, 2002), proceeding even when fathers never change a diaper, warm a bottle, or get up with a colicky child at night. Indeed, coparenting can proceed in families where the child's father does not reside with the child's mother at all (Ahrons, 1981;Black, Dubowitz, & Starr, 1999;Coley & Chase-Lansdale, 1999;Lerman, 1993;Maccoby, Depner, & Mnookin, 1990), as well as in families without fathers (Apfel & Seitz, 1991Patterson, 2002;Patterson et al, 2004) or mothers (Hamer & Marchioro, 2002;Hilton & Macari, 1997;Silverstein, 2002). To be sure, the division of childcare labor can provide a very important window into family commerce, as illustrated poignantly by Patterson et al (2004).…”
Section: Conceptual and Definitional Issues What Constitutes The Domamentioning
confidence: 99%
“…Indeed, coparenting can proceed in families where the child's father does not reside with the child's mother at all (Ahrons, 1981;Black, Dubowitz, & Starr, 1999;Coley & Chase-Lansdale, 1999;Lerman, 1993;Maccoby, Depner, & Mnookin, 1990), as well as in families without fathers (Apfel & Seitz, 1991Patterson, 2002;Patterson et al, 2004) or mothers (Hamer & Marchioro, 2002;Hilton & Macari, 1997;Silverstein, 2002). To be sure, the division of childcare labor can provide a very important window into family commerce, as illustrated poignantly by Patterson et al (2004). But conceiving of coparenting principally as the division of childcare labor provides a very limited perspective on the joint activities of adults responsible for the care and upbringing of children.…”
Section: Conceptual and Definitional Issues What Constitutes The Domamentioning
confidence: 99%
“…S'il me voyait maintenant, il serait un peu étonné, mais bon. (Adeline) Bien que non exempt de rapports de domination -lié notamment à l'inégalité de revenus ou de statut entre mère légale et mère non statutaire (Descoutures, 2010) -, le fonctionnement quotidien des couples montre une plus grande égalité que dans le modèle hétérosexuel traditionnel d'organisation domestique et des rôles parentaux (Patterson et al, 2004 ;Vecho et al, 2011). Quand elle est inégalitaire, la répartition des rôles n'est pas figée selon la ligne du genre -tâches féminines / tâches masculines -et n'est jamais jugée « normale » par les enquêtées, qui plaident la polyvalence et la renégociation possible de l'organisation en cas de changement d'emploi du temps de l'une ou l'autre.…”
Section: Abstract: Lesbian Parenting Heteronormativity Genderunclassified